Implementasi Reformasi Birokrasi Menuju Tata Kelola Pemerintahan Yang Baik: (Studi kasus: Pemerintah Kabupaten Kulon Progo) - Alim Muhammad Dwijaya; Ristanto Ristanto; Tri Hidayat; Mega Wati; Monika Monika (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Bureaucratic reform requires changes in mindset, work patterns and performance of every state apparatus. However, often the implementation is still far from what is expected from the objectives of implementing bureaucratic reform. The aim of this research is to determine the extent to which bureaucratic reform has been implemented in order to realize good governance in the Kulon Progo Regency Government. This research uses a qualitative methodology by prioritizing interviews and documentation. As for the research results, it can be concluded that the implementation of Kulon Progo district bureaucratic reform has gone well with the achievement of a "BB" score of 78.05 from the Ministry of Administrative and Bureaucratic Reform. Changes to the RB Road Map for 2023-2026 to ensure that RB management runs effectively, is more structured, systematic and massive to achieve bureaucratic reform targets. However, there are still obstacles in its implementation, including implementation that is not evenly distributed because it is still considered the task of certain work units only, partially and individually, participation of leaders and subordinates is not yet optimal and the implementation of reforms is still largely a formality.